Grafting's Function in Patients with Liver Intestinal and Multivisceral Transplantation. (July 2018) - Hidalgo Montes, Inmaculada; Sánchez, Miriam Nova; Gascón García, Maria; González Sacristán, Rocío; Magallares García, Lorena Nélida; Martinez-Ojinaga Nodal, Eva; Ramos Boluda, Esther; Moreno, Ana Miren Andrés; Hernández Oliveros, Francisco; López Santamaria, Manuel; Prieto Bozano, Gerardo
Abstract : Introduction: There are few studies of the intestinal graft function in medium and long term. Objectives: Assess the functional status of the graft in transplantation patients, once the immediate post-transplant has been overcome. Methodology: Patients who received a liver-intestinal or multivisceral transplantation were prospectively evaluated through cross-sectional data collection during a review. Clinical, analytical and functional variables are analyzed. Unstable patients with intercurrent processes were excluded. Results: Twenty-six patients were analyzed, 65.38% of them male. 21 with multivisceral graft (80.76%) and 5 liver-intestinal (19.23%). 7 multivisceral grafts were retransplantation (26.92%). The average age at transplantation was 1.73 + / 3.22 years (range: 7 months - 13 years). The average time post-transplant was 3.78 +/- 3.69 years (range 1.5 - 14 years). The indication for transplant was volvulus (19.23%), necrotizing enterocolitis (15.38%), gastroschisis (15.38%), pseudo-obstruction (11.53%), atresia (7.69%) intestinal ischemia (7.69%), epithelial dysplasia (7.69%), MartínezFrías syndrome (3.84%), mitochondrial disease (3.84%) and Hirschsprung's disease (3.84%). 96.15% of patients are autonomous oral-enteral. 1 (3.85%) maintains home parenteral nutrition. 15.38% receive enteral nocturnal nutrition. 3 patients (11.53%) maintain ostomy.Fecal alpha 1-antitrypsin was normal in 92.30% of patients. Fecal elastase was normal at 100%. Faecal fat excretion was normal in 84.61% of patients, only 4 (15.38%) with a moderate steatorrhea. Blood parameters were normal in 100% of patients, including serum citrulline levels with a mean of 37.16 μmol / L (range 21-74). Conclusion: 1. Patients with liver-intestinal and multivisceral transplantation have good graft function in medium and long term. 2. Most maintain digestive autonomy. 3. Although in some patients steatorrhea is observed, pancreatic function is normal in 100% of patients with a multivisceral transplantation that includes a pancreatic graft.